Mathematics in Medical Education - Yu.A, Balakin; B, Yunusov.X.; D.A, Yunusova (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates major points of the Mathematics in medical education. On this case, research has been pinpointed on both theoretical and methodological points of the medical education. In conclusion, research has noticed outcomes and shortcomings of the issue with the clear recommendations for the further.